2007
DOI: 10.1523/jneurosci.5433-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Neuromagnetic Brain Activity Underlying Concurrent Sound Perception

Abstract: Deficits in parsing concurrent auditory events are believed to contribute to older adults' difficulties in understanding speech in adverse listening conditions (e.g., cocktail party). To explore the level at which aging impairs sound segregation, we measured auditory evoked fields (AEFs) using magnetoencephalography while young, middle-aged, and older adults were presented with complex sounds that either had all of their harmonics in tune or had the third harmonic mistuned by 4 or 16% of its original value. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
60
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 37 publications
12
60
2
1
Order By: Relevance
“…ER-SAM analysis was applied to two previous MEG data sets ( [Alain et al, 2009] and [Alain and McDonald, 2007]). …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…ER-SAM analysis was applied to two previous MEG data sets ( [Alain et al, 2009] and [Alain and McDonald, 2007]). …”
Section: Methodsmentioning
confidence: 99%
“…In fact, when the evoked responses associated with a non-mistuned harmonic complex are subtracted from those associated with a mistuned one, a neural marker known as the object-related negativity (ORN) is revealed as a negative deflection 160-200 ms after sound onset (Alain et al, 2001). The ORN (and its magnetic counterpart, the ORNm) can be elicited whether listeners actively or passively listen to the sounds (Alain et al, 2001), is found in both young and old listeners (Alain and McDonald, 2007), and seems to be little affected by task difficulty or visual attention load (Dyson et al, 2005).…”
Section: And [Bidet-caulet Et Al 2007])mentioning
confidence: 99%
See 3 more Smart Citations